Urgensi Perlindungan Hukum bagi Konsumen Jasa Kesehatan dalam Praktik Tukang Gigi: Analisis Normatif dan Implementasi - Dandy Saputro; Rosita Candrakirana (Prosiding Seminar Nasional Ilmu Hukum, 2024)
The practice of dentists in Indonesia is an important concern in the health care system, especially regarding consumer protection. Dentists often provide services that exceed the limits of their authority, potentially endangering public health. This article aims to analyze the urgency of legal protection for consumers of health services in dental practices based on a normative perspective and the implementation of applicable regulations. This research uses normative juridical methods with statutory, conceptual and case approaches. The research results show that even though there are regulations such as Law no. 8 of 1999 concerning Consumer Protection and Minister of Health Regulation no. 39 of 2014, implementation is still less effective. This is caused by weak supervision, minimal public knowledge regarding consumer rights, and non-compliance by some dentists with regulations. Therefore, it is necessary to strengthen regulations, increase supervision by the government, and educate the public to realize optimal legal protection for consumers of health services.